PENGARUH PENAMBAHAN BATU KARANG SEBAGAI SUBSTITUSI AGREGAT HALUS DALAMPEMBUATAN PAVING BLOCK - Edy Gardjito; Agata Iwan Candra; Yosef Cahyo (U Karst, 2018)
Material exploitation, especially the use of sand as the main component of concrete, needs  to  be  reduced. The  purpose  of  this  research  is to find  out  the  value of  compressive strength   from   the addition of rocks to achieve compressive strength according to the standard mix  design  of  paving  blocks. This  research  was  conducted  at  the University's Civil Engineering Laboratory. Attending a trial and error method, the samples tested were cube with a size of 15 x 15 x 15 cm with 3 pieces with the quality of paving planned and K-225 or 18.675  MPa. The  method  of  making specimens  includes  semi-mechanics  using  a concrete mixer. Fractional waste The rock is crushed into small pieces and then put in messin abrassion to get smaller pieces of rock and become grains of sand. Test result obtained a percentage of 25% indicating a compressive strength of 22.1 MPa, 20.3 MPa, 19.9MPa, and has an average value   of 21.8   MPa. Then   the   results from the   substitution experience i increase   against compressive strength. Keywords: Coral, Fine Aggregate, Compressive Strength.  Eksploitasi material, terutama penggunaan pasir sebagai komponen utama beton, perlu dikurangi. Tujuan dari penelitian ini adalah untuk mengetahui nilai kekuatan tekan dari penambahan batuan untuk mencapai kekuatan tekan sesuai dengan desain campuran standar balok paving. Penelitian ini dilakukan di Laboratorium Teknik Sipil Universitas. Menghadiri metode coba-coba, sampel yang diuji adalah kubus dengan ukuran 15 x 15 x 15 cm dengan 3 buah dengan kualitas paving yang direncanakan dan K-225 atau 18,675 MPa. Metode pembuatan spesimen termasuk semi-mekanika menggunakan mixer beton. Limbah pecahan Batuan dihancurkan menjadi potongan-potongan kecil dan kemudian dimasukkan ke dalam abrasi untuk mendapatkan potongan batu yang lebih kecil dan menjadi butiran pasir. Hasil pengujian diperoleh persentase 25% yang menunjukkan kekuatan tekan 22,1 MPa, 20,3 MPa, 19,9MPa, dan memiliki nilai rata-rata 21,8 MPa. Kemudian hasil dari pengalaman substitusi saya meningkat terhadap kekuatan tekan Kata Kunci